Regulation of RNA binding proteins in trypanosomatid protozoan parasites - Romaniuk, María Albertina (2016)
Posttranscriptional mechanisms have a critical role in the overall outcome of gene expression. These mechanisms are especially relevant in protozoa from the genus Trypanosoma, which is composed by death threatening parasites affecting people in Sub-saharan Africa or in the Americas. In these parasites the classic view of regulation of transcription initiation to modulate the products of a given gene cannot be applied. This is due to the presence of transcription start sites that give rise to long polycistronic units that need to be processed costranscriptionally by trans-splicing and polyadenylation to give mature monocistronic mRNAs. Posttranscriptional mechanisms such as mRNA degradation and translational repression are responsible for the final synthesis of the required protein products. In this context, RNA-binding proteins (RBPs) in trypanosomes have a relevant role as modulators of mRNA abundance and translational repression by associating to the 3’ untranslated regions in mRNA. Many different RBPs have been proposed to modulate cohorts of mRNAs in trypanosomes. However, the current understanding of their functions lacks a dynamic view on the different steps at which these RBPs are regulated. Here, we discuss different evidences to propose regulatory events for different RBPs in these parasites. These events vary from regulated developmental expression, to biogenesis of cytoplasmic ribonucleoprotein complexes in the nucleus, and condensation of RBPs and mRNA into large cytoplasmic granules. Finally, we discuss how newly identified posttranslational modifications of RBPs and mRNA metabolism-related proteins could have an enormous impact on the modulation of mRNA abundance. To understand these modifications is especially relevant in these parasites due to the fact that the enzymes involved could be interesting targets for drug therapy.